Penilaian terhadap prestasi pelajar dan pengurusan program praktikum Universiti Utara Malaysia - Lim, Khong Chiu; Mahat, Nor Idayu; Hassan, Shahizan; Chik, Abdul Razak; Yahya, Mohd Azlan (UUM College of Arts and Sciences, 2010)
Purpose – The main focus of this study is to obtain the feedback from organisations with regards to the performance of UUM’s practicum students and practicum programme management. Method – A total of 438 organisations from different industrial backgrounds participated in this study. Data collection was carried out by using a uestionnaire which consists of five main components measuring respondents’ profile, students’ performance, practicum programme management, performances comparison with other universities, and the suitability of the practicum programme. Findings – The feedback obtaimed indicates that the participating organisations are satisfi ed with the performance of UUM students in preparing themselves for real work environment.The practicum management system that is practised by Centre for University-Industry Link (UIL) is also considered well organised and efficient. In addition, this study shows that there is no obvious difference between UUM students’ performance and students of other universities. Value – Several suggestions to improve students’ skills and practicum management system are identified.Information gathered can provide important insights from the perspective of organizations which can be valuable in improving the industrial training/practicum programmes as well as the overall academic programmes for future professionals and managers.